Incentivised experimental investigations of the affect heuristic - Ian J. Bateman; Paul Slovic; Chris Starmer (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
In recent years there has been increasing interest in using the related concepts of affect and evaluability to understand a wide range of decision behaviours. However, a common feature of studies to date is that they have adopted hypothetical payoff designs. Such an approach is open to criticisms of non-consequentiality. In this paper we address this criticism, presenting a series of incentivised, real payoff, experimental studies examining the roles of affect and, the related concept of evaluability in judgments and decisions across a range of contexts including money gambles and the purchase of and preference for various market goods. We demonstrate that the affect heuristic remains a feature of decision making in the contexts considered within this experiment.
Keywords: 330; Affect heuristic; auction; evaluability; real payments